THE INFLUENCE OF DYNAMIC CAPABILITIES AND INNOVATION ON THE PERFORMANCE OF THE ELECTRICAL AND ELECTRONICS INDUSTRY IN THAILAND - Wongwanich, Boontharika; Laohavichien, Tipparat (RMUTT Global Business and Economics Review, 2023)
The purpose of this study was to examine the influence of dynamic capability and innovations on the performance of the electrical and electronics industry in Thailand. The sample group consisted of entrepreneurs in the electrical and electronics industry in Thailand which had registered as a juristic person with the Ministry of Commerce. The respondents were 336 executives employees or organizational representatives with understanding of the overall management in the organization. Questionnaires were used to collect data. Quantitative data analysis was used to analyze statistics such as percentages, arithmetic mean, and standard deviation. To analyze structural equation modeling (SEM) were employed. The study revealed that the developed model was consistent with the empirical data. The harmonized indices included Chi-square = 62.492, df = 51, p-value = 0.130, Chi-square/df = 1.225, GFI = 0.975, AGFI = 0.948, NFI = 0.975, CFI = 0.995, RMSEA = 0.026. Thus, dynamic capability, organization-wide quality management, and innovation had a positive direct influence on the performance of the electrical and electronics industry in Thailand with statistical significance at the 0.05 level